2021
DOI: 10.1007/s11571-021-09748-0
|View full text |Cite
|
Sign up to set email alerts
|

LEDPatNet19: Automated Emotion Recognition Model based on Nonlinear LED Pattern Feature Extraction Function using EEG Signals

Abstract: Electroencephalography (EEG) signals collected from human brains have generally been used to diagnose diseases. Moreover, EEG signals can be used in several areas such as emotion recognition, driving fatigue detection. This work presents a new emotion recognition model by using EEG signals. The primary aim of this model is to present a highly accurate emotion recognition framework by using both a hand-crafted feature generation and a deep classifier. The presented framework uses a multilevel fused feature gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The experimental analysis demonstrated that the accuracy is increased with the use of fuzzy logic. On the other hand, many articles did not use data fuzzification in the preprocessing phase and obtained outstanding classification results which outperformed the state-of-the-art methods such as [24][25][26]. In fact, Zhang et al [24] demonstrated that the experimental results showed the excellent performance of the proposed model in comparison to the existing state-of-the-art models.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…The experimental analysis demonstrated that the accuracy is increased with the use of fuzzy logic. On the other hand, many articles did not use data fuzzification in the preprocessing phase and obtained outstanding classification results which outperformed the state-of-the-art methods such as [24][25][26]. In fact, Zhang et al [24] demonstrated that the experimental results showed the excellent performance of the proposed model in comparison to the existing state-of-the-art models.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In fact, Zhang et al [24] demonstrated that the experimental results showed the excellent performance of the proposed model in comparison to the existing state-of-the-art models. Furthermore, Tuncer et al [25] stated that the best classification accuracy of the proposed Led-Pattern model named: LEDPatNet19 for the GAMEEMO dataset attained 99.29%. Moreover, Mohebbanaaz et al [26] showed the superior performance of their proposed classifier with classification results equivalent to 98.77%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Emotion classification, where the real moods of the subject(s) are automatically classified using machine learning techniques [37][38][39], is a growing research field. Many emotion classification models in the literature use various input data: facial images, speech, biophysical signals (e.g., electroencephalography), or functional magnetic resonance images [17,40,41], [42].…”
Section: Contributionsmentioning
confidence: 99%
“…These cross-subject problems with large and complex data can be handled in a much better way by employing deep learning techniques [10,21]. The studies reported in [22][23][24][25][26] quantified EEG features to recognize neurological deteriorations according to the task because of stroke and estimate the biomarkers to differentiate between healthy adults and ischemic stroke patients.…”
Section: Introductionmentioning
confidence: 99%